Electronic Land Deed Issuance by Land Deed Officials in Indonesia: Regulation, Data Protection, and Legal Certainty - Gloria Gita Putri Ginting; Henry Aspan; Muhammad Juang Rambe (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Digital transformation in land registration in Indonesia triggers a conflict of laws regarding the electronic issuance of deeds by Land Deed Officials (Pejabat Pembuat Akta Tanah / PPAT). This study aims to analyze the disharmony between Government Regulation Number 18 of 2021 and Government Regulation Number 37 of 1998 concerning the prerequisite of physical presence, its implications for personal data protection governance, and to formulate a regulatory architecture through a comparative study. The method employed is normative legal research utilizing statutory, conceptual, and comparative approaches. This study applies a jurimetric instrument through the Legal Reliability Index (LRI) modeling to quantitatively measure the degree of evidentiary reliability of deeds. The results indicate that non-compliance with the physical presence requirement degrades the status of an authentic deed to a private deed (akta di bawah tangan) pursuant to Article 1869 of the Indonesian Civil Code. Simulation of the LRI formula demonstrates that procedural compliance regarding physical presence serves as the primary determinant maintaining the independent validity of the deed, while concurrently limiting the scope of the PPAT's liability from cyber system failure risks at the Land Office under the Personal Data Protection Law. This study recommends the adoption of a hybrid model based on a cautionary approach, drawing from practices in Germany. Physical presence remains mandatory for the substance of rights transfer to validate intent, whereas the archiving of original deeds (minuta akta) is centrally computerized. Amendments to the PPAT Position Regulations are necessary to align technological efficiency with formal civil law certainty.